2021
DOI: 10.3390/ph14060500
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish, an In Vivo Platform to Screen Drugs and Proteins for Biomedical Use

Abstract: The nearly simultaneous convergence of human genetics and advanced molecular technologies has led to an improved understanding of human diseases. At the same time, the demand for drug screening and gene function identification has also increased, albeit time- and labor-intensive. However, bridging the gap between in vitro evidence from cell lines and in vivo evidence, the lower vertebrate zebrafish possesses many advantages over higher vertebrates, such as low maintenance, high fecundity, light-induced spawnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 153 publications
0
12
0
Order By: Relevance
“…The zebrafish has emerged as a universal biotechnological platform for effective and safe drug discovery owing to their genetic, molecular, and immunological similarity to humans, and highly correlated response to pharmaceuticals including anticancer compounds [68][69][70] . The use of this model system simplifies the path of novel bioactive compounds to clinical trials and reduce the failure of potential therapeutics at later stages of testing [71,72] . Herein, we found that none of two novel HDAC inhibitors caused lethal effect at the doses up to 100 µM after the 5-day treatment (LC 50 > 100 µM) (Fig.…”
Section: Bdr-8 Decreases Migration and Invasion Of Triple Negative Br...mentioning
confidence: 99%
“…The zebrafish has emerged as a universal biotechnological platform for effective and safe drug discovery owing to their genetic, molecular, and immunological similarity to humans, and highly correlated response to pharmaceuticals including anticancer compounds [68][69][70] . The use of this model system simplifies the path of novel bioactive compounds to clinical trials and reduce the failure of potential therapeutics at later stages of testing [71,72] . Herein, we found that none of two novel HDAC inhibitors caused lethal effect at the doses up to 100 µM after the 5-day treatment (LC 50 > 100 µM) (Fig.…”
Section: Bdr-8 Decreases Migration and Invasion Of Triple Negative Br...mentioning
confidence: 99%
“…The zebrafish has emerged as a universal biotechnological platform for effective and safe drug discovery owing to their genetic, molecular, and immunological similarity to humans, and highly correlated response to pharmaceuticals including anti-cancer compounds [51][52][53] . The use of this model system simplifies the path of novel bioactive compounds to clinical trials and reduce the failure of potential therapeutics at later stages of testing [54,55] .…”
Section: Toxicity Assessment In Vivo Using the Zebrafish Modelmentioning
confidence: 99%
“…The lower vertebrate zebrafish possesses many advantages over higher vertebrates, such as low maintenance, high fecundity, light-induced spawning, transparent embryos, short generation interval, rapid embryonic development, fully sequenced genome, and some phenotypes similar to human diseases [ 14 ]. Such merits have popularized the zebrafish as a model system for biomedical and pharmaceutical studies, including drug screening [ 15 , 16 ]. Additionally, zebrafish are regarded as an important research tool for studying LSD [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%